2012
DOI: 10.1002/j.0022-0337.2012.76.6.tb05316.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profile and Future Expectations of Students Enrolled in a Turkish Private Dental School

Abstract: The purposes of this study were to obtain information about the social and demographic proile of students enrolled in the irst private Turkish dental school, to gather information regarding the reasons for their preferences, and to obtain data about their career expectations. Questionnaires were distributed to 278 students; 229 returned the survey for an overall response rate of 82 percent. Of the respondents, 145 (65.5 percent) were females and seventy-ive (34.5 percent) were males; they had an average age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
44
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 20 publications
16
44
1
1
Order By: Relevance
“…According to a recent survey by the FDI geographical mal-distribution of dentists is a problem regardless of the economic development of a country and migration to larger cities is an international trend [ 21 ]. A majority of this study’s students preferred to work in urban areas, a finding that aligns with other studies [ 4 , 21 , 31 , 35 , 36 , 49 , 50 ] with only 10 % intending to work in rural areas after graduation. This will not benefit the 80 % of Nepalese people that live in rural areas [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to a recent survey by the FDI geographical mal-distribution of dentists is a problem regardless of the economic development of a country and migration to larger cities is an international trend [ 21 ]. A majority of this study’s students preferred to work in urban areas, a finding that aligns with other studies [ 4 , 21 , 31 , 35 , 36 , 49 , 50 ] with only 10 % intending to work in rural areas after graduation. This will not benefit the 80 % of Nepalese people that live in rural areas [ 51 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results show that a majority of the dentistry students are from families with greater educational achievement, which can be a proxy for social position. As with other studies [ 31 , 32 ] students enrolled in higher education tend to be from families of higher social position, which is evidenced by the fact that a majority of the students (46 %) in this study reported to be a part of the Brahmin, Chhetri or Newar caste. According to Central Bank of Nepal (2013) Newar, Brahmin and Chhetri have the highest monthly earning in Rupees per month compared to other ethnic groups or caste and their level of education is higher [ 33 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Já no presente estudo, as maiores frequências na amostra foram as áreas de Ortodontia, seguido de Implantodontia e Prótese. As especialidades clínicas, em especial Ortodontia e Cirurgia-oral, podem ter maior prestígio na comunidade odontológica devido ao maior retorno financeiro que proporcionam, por isso possuem bastante procura pelos dentistas (Tanalp et al, 2012).…”
Section: Média Dos Resultados Do Questionário Dssunclassified